The Troubles With Postmodernism - Morawski, Stefan (Routledge, 2013)
In this original and eye-opening study, Stefan Morawski sheds light on the often confused debate about postmodernism, postmodernity and human values. Drawing upon a wide range of evidence from the experience of everyday life in the sciences, religion, visual arts, literature, film, television and contemporary music, The Troubles with Postmodernism is an indispensable guide to our understanding and evaluation of contemporary literature.